Controlling micropollutants in tertiary municipal wastewater by O3/H2O2, granular biofiltration and UV254/H2O2 for potable reuse applications. (January 2020) - Piras, F.; Santoro, O.; Pastore, T.; Pio, I.; De Dominicis, E.; Gritti, E.; Caricato, R.; Lionetto, M.G.; Mele, G.; Santoro, D.
Abstract: A comprehensive pilot study was carried out to experimentally assess the potential of newly developed treatment trains integrating two-stage AOPs and biofiltration to reach potable reuse water quality standards from municipal wastewater. The processes consisted of a two-stage AOPs with (carbon or limestone) biofiltration, the first AOP (O3 /H2 O2 ) serving as pre-treatment to biofiltration and the second AOP (UV254 /H2 O2 ) serving as post-biofiltration finishing step to ensure advanced disinfection. A comprehensive monitoring campaign was put in place resulting from the combination of targeted, non-targeted and suspect screening measurements. It was found that 13 organic micropollutants were detected from a list of 219 suspects although at ng/L level only. For the treatment conditions piloted in this study (O3 = 13 ± 0.5 mg/L, H2 O2 = 11 ± 0.4 mg/L for the O3 /H2 O2 process, and UV = 410 ± 63.5 mJ/cm 2, H2 O2 = 5 mg/l for the UV254 /H2 O2 process), it was possible to estimate the overall removal efficacy for each unit process, which was found to follow this order: RO (99%) > BAC (87%) > O3 -H2 O2 (78%) > BAL (67%) > UV/H2 O2 (43%) > AOP contact chamber (19%) > UF(0%), with the treatment train integrating two AOPs and granular biofiltration with activated carbon (O3 /H2 O2 + BAC + UV254 /H2 O2 ) showing superior performance with a 99% abatement in total micropollutants. No ecotoxicologically-positive response was generally observed for any of the effluent samples from the tested trains, even when pre-concentration factors up to 100–1000 times were employed to increase the sensitivity of the bioassay methods. Highlights: Biofiltration-based treatment schemes are a viable alternative to the membrane-based schemes. Peroxidation by O3 /H2 O2 is a very efficient pre-treatment method prior to biofiltration or reverse osmosis. No or very limited response to ecotoxicological tests or byproduct formation was observed in this study.